Interaction between the non-alcoholic fatty liver disease fibrosis score and vitamin D deficiency on left ventricular hypertrophy and impaired diastolic function in patients with type 2 diabetes mellitus - Li, Yun-Ming; Huang, Jia-Yi; Guo, Ran; Li, Shi-Ming; Chen, Cong; Wu, Min; Wang, Run; Liu, Ming-Ya; Yiu, Kai-Hang (Diabetology and metabolic syndrome, 2025)
The present study aimed to evaluate the effect of Non-Alcoholic Fatty Liver Disease Fibrosis Score (NFS), vitamin D deficiency, and their interaction on the Left Ventricle (LV) structure and diastolic function in type 2 diabetes mellitus (T2DM) patients. A total of 595 T2DM patients were recruited and stratified according to NFS grades (low, intermediate, and high) and the level of serum 25(OH)D (with and without vitamin D deficiency). Parameters of LV structure and diastolic dysfunction were measured by echocardiography. The association between NFS and LV structure and diastolic function was assessed using multivariable linear regression models stratified by vitamin D levels. Left ventricular hypertrophy (LVH) was more prevalent in patients with high NFS compared to those with low and intermediate NFS (41.0 vs 14.0% and 9.0%, P < 0.001). The average E/e' was higher in patients with intermediate and high NFS, as compared to those with low NFS. Within the high NFS group, patients with vitamin D deficiency exhibited significantly higher left ventricular mass index (LVMI) and average E/e' compared to those without vitamin D deficiency. An interaction between vitamin D and NFS groups was found on both LVMI (P for interaction = 0.008) and average E/e' (P for interaction = 0.001). NFS and vitamin D deficiency are associated with an increased risk of LVH and impaired diastolic function in patients with T2DM. Notably, the impact of vitamin D deficiency on these parameters is more pronounced in individuals with a high NFS score.